STUDI KONSISTENSI PERENCANAAN DAN PENGANGGARAN PEMBANGUNAN MANUSIA DI KABUPATEN KARANGASEM - Sonia Rakhma Maulani (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2022)
Consistency between planning and budgeting plays a vital role in ensuring the realization of regional development goals. This research aims to measure the level of consistency between human development planning and budgeting in Karangasem Regency during the period of 2017-2020 as well as identify the factors that influence these achievements. The results showed that the level of consistency was